2013
DOI: 10.1177/001979391306600505
|View full text |Cite
|
Sign up to set email alerts
|

The Diffusion of Pay for Performance across Occupations

Abstract: Standard-Nutzungsbedingungen:Die Dokumente auf EconStor dürfen zu eigenen wissenschaftlichen Zwecken und zum Privatgebrauch gespeichert und kopiert werden.Sie dürfen die Dokumente nicht für öffentliche oder kommerzielle Zwecke vervielfältigen, öffentlich ausstellen, öffentlich zugänglich machen, vertreiben oder anderweitig nutzen.Sofern die Verfasser die Dokumente unter Open-Content-Lizenzen (insbesondere CC-Lizenzen) zur Verfügung gestellt haben sollten, gelten abweichend von diesen Nutzungsbedingungen die in… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
1
1
1
1

Citation Types

0
38
0

Year Published

2015
2015
2024
2024

Publication Types

Select...
9
1

Relationship

2
8

Authors

Journals

citations
Cited by 30 publications
(38 citation statements)
references
References 53 publications
0
38
0
Order By: Relevance
“…Further, international research has found that human resource practices that threaten or support those needs-thus creating the pressures leading to the curvilinear performance-turnover relationship-exist in a wide range of countries. Pay-for performance systems, which reward the top and penalize the bottom, have been studied in culturally divergent countries, such as China (Buck, Liu, & Skovoroda, 2008;Du & Choi, 2010), India (Kingdon & Teal, 2007), Italy (Origo, 2009), Japan (Beatty, McCune, & Beatty, 1988;Hatvany & Pucik, 1981), Rwanda (Kalk, Paul, & Grabosch, 2010), and Spain (Bayo-Moriones, Galdon-Sanchez, & Martinez-de-Morentin, 2010). The spread of U.S.-based multinational corporations has also brought pay-for-performance norms around the world, as at the corporation studied by DeVoe and Iyengar (2004) that used the system in Argentina, Brazil, Mexico, Philippines, Taiwan, and the United States.…”
Section: Reasons For the Generalizability Of The Theorymentioning
confidence: 99%
“…Further, international research has found that human resource practices that threaten or support those needs-thus creating the pressures leading to the curvilinear performance-turnover relationship-exist in a wide range of countries. Pay-for performance systems, which reward the top and penalize the bottom, have been studied in culturally divergent countries, such as China (Buck, Liu, & Skovoroda, 2008;Du & Choi, 2010), India (Kingdon & Teal, 2007), Italy (Origo, 2009), Japan (Beatty, McCune, & Beatty, 1988;Hatvany & Pucik, 1981), Rwanda (Kalk, Paul, & Grabosch, 2010), and Spain (Bayo-Moriones, Galdon-Sanchez, & Martinez-de-Morentin, 2010). The spread of U.S.-based multinational corporations has also brought pay-for-performance norms around the world, as at the corporation studied by DeVoe and Iyengar (2004) that used the system in Argentina, Brazil, Mexico, Philippines, Taiwan, and the United States.…”
Section: Reasons For the Generalizability Of The Theorymentioning
confidence: 99%
“…Among studies which substantively cited any of the three articles of interest, the number of those taking a systematic view of all four quadrants (N ¼ 93) is higher than the number of those focusing on an individual quadrant (N ¼ 45). This suggests that researchers are more Beatty et al, 2003Bayo-Moriones et al, 2013Gelens et al, 2013Nieves & Quintana, 2018Lepak & Snell, 2002 Gonz alez & Verano-Tacorante, 2004De Vos & Dries, 2013McDonnell et al, 2016Schmidt, Pohler, et al, 2018Purcell et al, 2004Kulkarni & Ramamoorthy, 2005Kang et al, 2007Bryant & Allen, 2009Zhou et al, 2012 2. Individual Quadrant of the HR Architecture 2.1 Q1: for HC with High Uniqueness and High Value 9 1 0 1 2 L opez-Cabrales et al, Nijs et al, 2014Chuang et al, 2016Lepak et al, 2007Boon & Kalshoven, 2014Tlaiss et al, 2017Nesheim et al, 2007 Way et al, 2015…”
Section: Resultsmentioning
confidence: 99%
“…Regarding the size, the most part of respondents (about 70%) work in companies with more than 250 employees. This is remarkable since literature has identified the large size of the business as a key determinant of the decision to adopt complex HRM practices, including performance appraisal (Bayo-Moriones et al, 2013) as well as of the decision to embrace digital transformation (McKinsey Global Institute, 2016).…”
Section: Methodsmentioning
confidence: 99%